Wireless passive sensor based on microstrip antenna for metal crack detection and characterization. (18th March 2019) - Dong, Helei; Kang, Wenfang; Liu, Longfei; Wei, Kailong; Xiong, Jijun; Tan, Qiulin
Abstract: This paper proposes a wireless passive sensor based on microstrip antenna theory for detecting and characterizing the direction and width of metal cracks. The sensor was fabricated on a high-temperature ceramic substrate (99% Al2 O3 ) via screen-printing using commercially available metallic silver paste. The direction of the crack was determined by the change in the two different resonant frequencies of the sensor, and the width of the metal crack was characterized by the offset of the resonant frequency of the sensor. The frequency sensitivity for horizontal and vertical cracks is 3.5 MHz/0.1 mm and 4.5 MHz/0.1 mm, respectively. The results show that the sensor can detect the direction of the crack, well characterize the crack width, and even detect sub-millimeter cracks.